Israel as the Living Temple of God (Exod 19:5-6) - Lemański, Janusz Adam (Verbum Vitae, 2023)
Exod 19:3–8 and the description of Israel’s identity as a chosen nation bound by a covenant with YHWH (Exod 19:5–6: special possession, kingdom of priests, holy nation) have much in common both with statements known from deuteronomistic and priestly texts as well as from the so-called School of Holiness. This multiplicity of thematic, conceptual and linguistic connections makes the source classification and dating of this text quite difficult. The only consensus today is that it was written at the earliest just after the Babylonian exile. In this paper, the description of Israel’s identity in Exod 19:5–6 is linked to the priestly concept of the portable sanctuary, in which the specific location of the sanctuary (the sanctuary in the desert) is no longer important and not only the king or the priests are responsible for it, but the entire nation. This vocation is to be realized by the nation’s attitude of faithfulness to God (Exod 19:5a) in everyday life. In this way, sacred space in Israel goes beyond the walls of the temple and even Jerusalem (as according to Ezechiel), nor is it any longer limited to selected moments (visit to the sanctuary), but encompasses the entire life of the nation in all its aspects